Groundwater mineralisation processes in Mediterranean semi-arid systems (Cap-Bon, North east of Tunisia): hydrogeological and geochemical approaches - Zghibi, Adel; Zouhri, Lahcen; Tarhouni, Jamila; Kouzana, Lamia (Hydrological processes, 2013)
The groundwater of the Korba plain represents major water resources in Tunisia. The Plio‐Quaternary unconfined aquifer of the Cap‐Bon (north‐east Tunisia) is subject to the intensive agricultural activities and high groundwater pumping rates due to the increasing of the groundwater extraction. The degradation of the groundwater quality is characterized by the salinization phenomena. Groundwater were sampled and analysed for physic‐chemical parameters: Ca2+, Mg2+, Na+, K+, Cl‐, SO42‐, HCO3‐, NO3‐, pH, electrical conductivity (EC), and the temperature (T°). The hydrochemical analysis is coupled with the calculation of the saturation indexes (SI gypsum, SI halite, SI calcite and SI dolomite), ionic derivation and with the ion correlations compared to chloride concentrations: Na+/ Cl‐, Ca2+/ Cl‐ and Mg2+/ Cl‐ ratios. Seawater fractions in the groundwater were calculated using the chloride concentration. Those processes can be used as indicators of seawater intrusion progression. EC methods were also conducted to obtain new informations on the spatial scales and dynamics of the fresh water–seawater interface of coastal groundwater exchange. The mixing zone between freshwater and saltwater was clearly observed from the EC profile in the investigated area where a strong increase in EC with depth was observed, corresponding to the freshwater and saltwater interface. Results of hydrochemical study revealed the presence of direct cation exchange linked to seawater intrusion and dissolution processes associated with cations exchange. These results, together with EC investigation, indicated that the groundwater is affected by seawater intrusion and is still major actor as a source of salinization of the groundwater in Korba coastal plain. Further isotopic and hydrological investigations will be necessary to identify and more understood the underlying mechanisms. Copyright © 2012 John Wiley & Sons, Ltd.